Poetry and the Art of Meditation: Going behind the Symbols - Stan Scott (Journal of the Assembly for Expanded Perspectives on Learning, 2005)
Combining reader-response theory with spiritual teachings, this article explores how reading poetry may serve as an introduction to the art of meditation.